Relations of Recognition in Feminised Work Scenarios. a Proposal of Axes of Analysis Based on the Case of Female Workers in the Chilean Retail Industry - Cordoba-Calquin, C (UNIV CATOLICA TEMUCO, 2021)
This article discusses the dynamics of recognition in feminized jobs, particularly in the service sector. Based on the theory of recognition by Honneth and other authors, three axes of analysis of the dynamics of recognition are presented, formed both from socio-technical configurations of work and as a function of social structures of gender and class. The group of cashiers from large supermarket chains and department store saleswomen in Santiago de Chile is taken as a case.